Pendidikan Kesehatan Pijat Bayi Usia 3-6 Bulan Dapat Mempengaruhi Sikap Ibu : Health Education Massage for Babies Ages 3-6 Months Can Influence Mother's Attitude - Siti Syamsiah; Rizky Arliyati; Rosmawaty Lubis (MPI Press, 2022)
Background: The World Health Organization (WHO) in 2019 reported that the prevalence data for infants with growth and development disorders was 28.7% and Indonesia was included in the third country with the highest prevalence in the Southeast Asia region. Globally, about 20-40% of infants aged 0-2 years have problems with delays in the growth process due to a lack of stimulus in infants and a lack of mother's knowledge about baby massage. The problems of infant growth and development in developed countries include America 12-16%, Argentina 22% and Hongkong 23%. Objective: To determine the effect of health education on baby massage aged 3-6 months on the attitude of mothers at BPM X Tangerang City. Method: The research method used a quasi eksperimental. The study population of all mothers who have infants aged 3-6 months in BPM X Tangerang City regency as many as 52 respondents. The technique used in Proportional Sampling, The instrument used in data collection is questionnaire. Data analysis using Paired T-Test. Results: From the results of the study before being given health education about baby massage aged 3-6 months, almost all of them had a negative attitude 41 (78.8%), and after being given health education about baby massage aged 3-6 months most of the respondents had a positive attitude 33 (63.5%). The results of the bivariate analysis showed that the average pre-test value was 1.210 with St. Deviation is 0,412 while for the post-test value obtained 1.630 with St.Deviation 0.486. Conclusion: That there is a significant effect on the provision of health education about infant massage aged 3-6 months on the mother's attitude with a p-value 0.000.